HAM Beragama dalam perspektif Filsafat Ilmu Hukum - Fatriansyah, Fatriansyah; Alamsyah, Bunyamin (Universitas Batanghari Jambi, 2024)
Religious human rights have a very important position. Religious Human Rights are autonomous as a consequence of God-given nature for human glory. In modern thought, these natural rights can be formulated humanistically through rational reasoning without having to relate to the existence of God. Therefore, human rights must be fully given the same freedom and opportunity.